More Than Four Walls: The Meaning of Home in Home Birth Experiences - Emily Burns (Social Inclusion, 2015)
The “home versus hospital” as places of birth debate has had a long and at times vicious history. From academic literature to media coverage, the two have often been pitted against each other not only as opposing physical spaces, but also as opposing ideologies of birth. The hospital has been heavily critiqued as a site of childbirth since the 1960s, with particular focus on childbirth and medicalisation. The focus of much of the hospital and home birthing research exists on a continuum of medicalisation, safety, risk, agency, and maternal and neonatal health and wellbeing. While the hospital birthing space has been interrogated, a critique of home birthing space has remained largely absent from the social sciences. The research presented in this article unpacks the complex relationship between home birthing women and the spaces in which they birth. Using qualitative data collected with 59 home birthing women in Australia in 2010, between childbearing and the home should not be considered as merely an alternative to hospital births, but rather as an experience that completely renegotiates the home space. Home, for the participants in this study, is a dynamic, changing, and even spiritual element in the childbirth experience, and not simply the building in which it occurs.